New Aulacoseira species (Bacillariophyta) from the Argentinean Patagonia and re-examination of type material of Melosira perpusilla Frenguelli - García, M. Luján; Morales, Eduardo A.; Guerrero, José M.; Tremarin, Priscila I.; Maidana, Nora I. (Phytotaxa, 2019)
We present a detailed morphological analysis with light and scanning electron microscopy of two new small Aulacoseira species occurring in lacustrine sediments from small lakes in the provinces of Santa Cruz and Neuquén (Patagonia, Argentina). These species differ from similar taxa by unique combinations of characters. Aulacoseira lauquenensis sp. nov. can be differentiated by its broad collum, deep and solid ringleist and presence of short, spatulate and forked-tip spines. Aulacoseira liucoensis sp. nov. is distinguished by the presence of a marginal row of valve face areolae, straight mantle rows of coarse areolae, developed collum, protruding ringleist and conical, anchor-tip spines. Additionally, we re-examine the type material of Melosira perpusilla Frenguelli and present an analysis of its identity.